A Prognostic Autophagy-Related Long Non-coding RNA (ARlncRNA) Signature in Acute Myeloid Leukemia (AML) - Zhao, Chunxia; Wang, Yulu; Tu, Famei; Zhao, Shuai; Ye, Xiaoying; Liu, Jing; Zhang, Juan; Wang, Zifeng (Frontiers in Genetics, 2021)
Abstract Background: Some studies have proven that autophagy and lncRNA play important roles in AML. Several autophagy related lncRNA signatures have been shown to affect the survival of patients in some other cancers. However, the role of autophagy related lncRNA in AML has not been explored yet. Hence, this study aims to find an autophagy related lncRNA signature which can affect survival for AML patients. Method: A Pearson correlation analysis, a Kaplan-Meier survival curve, a univariate cox regression and a multivariate cox regression were performed to establish an autophagy related lncRNA signature. A univariate cox regression, a multivariate cox regression, a Kaplan-Meier survival curve and a ROC curve were applied to confirm if the signature is an independent prognosis for AML patients. The relationship between the signature and the clinical features was explored by using a T test. Gene Set Enrichment Analysis (GSEA) was used to investigate the potential tumor related pathways. Results: A four-autophagy related lncRNA (MIR133A1HG, AL359715.1, MIRLET7BHG and AL356752.1) signature was established. The high risk score based on signature was related to the short survival time of AML patients. The signature was an independent factor for prognosis for AML patients (HR=1.684, 95%CI=1.324-2.142, P<0.001). The signature was correlated with age, leukocyte numbers, and FAB (M3 or non-M3). P53, IL6/JAK/STAT3, TNF-α, INF-γ, and IL2/STAT5 pathways might contribute to the differences between the risk groups based on signature in AML. Conclusion: The four autophagy related lncRNAs and their signature might be novel biomarkers predicting the survival of AML patients. Some biological pathways might be the potential mechanisms of the signature for the survival of AML patients.